Policy Frameworks and Citizens’ Use of Fintech Solutions: The Pros and Cons in Egypt - Al-Mohamady, Salma (AUC Knowledge Fountain, 2024)
This thesis provides a comprehensive analysis of the significant influence of financial technology (FinTech) on the banking industry, consumer finance, and economic growth. It specifically concentrates on the swiftly changing FinTech environment in Egypt. The study investigates the impact of incorporating advanced technologies on worldwide financial practices, which has significantly transformed traditional banking models and facilitated the emergence of inventive financial services. The transition is clearly apparent in Egypt, where the expansion of FinTech has been driven by advances in regulations, adaptation to technology, and a population that is becoming more comfortable with digital solutions. Using a combination of quantitative surveys and qualitative insights, this study examines customer habits, preferences, and perceptions towards FinTech in comparison to traditional banking systems during the past five years. The study reveals several significant findings. First, it highlights a notable change in consumer preferences towards FinTech solutions, which can be attributed to their improved accessibility, efficiency, and user-centric design. Additionally, the study highlights the impact of FinTech on the financial services industry. It acknowledges the positive aspects of innovative and flexible financial services, but also raises concerns about the potential rise in consumer debt-burden ratios. This emphasizes the importance of promoting financial literacy and responsible borrowing practices. The analysis addresses the regulatory environment and examines how current policies and frameworks impact the operation and expansion of FinTech companies in Egypt. The findings underscore the importance of maintaining an equilibrium between promoting innovation and safeguarding consumer interests. This underscores the need for regulatory practices that are flexible and forward-thinking, in order to facilitate the sustainable development of the FinTech industry.